Effects of surgical atrial septal defect closure operation on the frontal QRS-T angle (Annals of Medical Research, 2021)
Aim: A new marker has been found for ventricular repolarization and depolarization heterogeneity, which is the frontal plane QRS-T [f(QRS-T)] angle between the directions of ventricular depolarization (QRS axis) and repolarization (T axis). Adverse cardiac outcomes can be detected based on observation of the f(QRS-T) angle.In atrial septal defect (ASD) patients, surgical closure of ASD is safer and more effective than its percutaneous closure with higher popularity in the last two decades. Nevertheless, we have scarce information about the impact of ASD closure on cardiac autonomic function and heart repolarization.The aim of the study is to investigate the potential effect of ASD operation on the f(QRS-T) angle and cardiac repolarization parameters.Materials and Methods: In our retrospective study design we sampled a total of 24 patients who underwent ASD closure surgery operation between December 2011 and January 2019. Preoperative and postoperative 6 week ECG parameters including the f(QRS-T) of the patients were compared.Results: When pre- and postoperative ECG parameters were compared, no statistically significant difference was found in QT interval (p=0.079), adjusted QT interval (p=0.079), Tpe interval (p=0.150) and Tpe/QTc ratio (p=0.696). An improvement was found in QRS duration (p=0.035), p wave duration (p0.001) and f(QRS)-T angle (p0.001).Conclusion: In our study, it was observed that surgical ASD closure operation was associated with heart repolarization parameters and improvement in f(QRS-T).
Keywords: Arrhythmia; atrial septal defect; Frontal QRS-T angle